The two faces of leuconostoc mesenteroides in food systems - Paula, Aline T. de [UNESP]; Jeronymo-Ceneviva, Ana Beatriz [UNESP]; Todorov, Svetoslav D.; Penna, Ana Lucia B. [UNESP] (Taylor &francis Inc, 2015)
Leuconostoc mesenteroides is a lactic acid bacterium (LAB) that has been isolated from different sources. Some of its strains are able to produce bacteriocins, and most of them belong to class IIa and shows anti-Listeria activity. Additionally, Lc. mesenteroides species can be a probiotic candidate; promising studies have shown the potential of this species to survive and grow under various stress conditions present in the gastrointestinal tract. On the other hand, this microorganism can cause spoilage in some types of food matrices, and scarce reports have shown the pathogenic potential of this species. In this review, we focus on an overview of Lc. mesenteroides bacteriocin-producing strains and their probiotic potential, in contrast with Lc. mesenteroides spoilage and pathogenic cases reported in the literature.
Keywords: Probiotic; Pathogenic; Bacteriocins; Biopreservation; Spoilage